"Corporal Punishment and the Grace of God": The Archaeology of a Nineteenth Century Girls' Reformatory in South Australia. Issue 3 (27th August 2015) - de Leiuen, Cherrie
ABSTRACT: The site of St John's provides a unique insight into the internal dynamics and materiality of a nineteenth century Catholic girls' reformatory and the silent lives of the young women, both inmates and nuns, who were confined there. The organisation and material culture of the site reflects the intersection of Australian colonial, Catholic and "middle‐class" ideologies. This institution's purpose was to reform through the imparting of a Catholic hegemony of "appropriate" female behaviour and sexuality; this hegemony was supported by enculturation, which included the altering, confining, decorating and ordering of the St John's space. The site and its assemblage, whilst small, demonstrate the framework for, and materiality of, the reformatory system that was underpinned by deep traditions of female confinement based in Catholic institutional models. Gender as a social process is key to reading and interpreting the materiality of the St John's Reformatory for girls. Gender frames, informs and contextualises the materiality of the site, its aims, its operation and thus its archaeological interpretation. Further, the ideological gender roles and regimes related through historical accounts provide the context for the embeddedness of gender in the material culture found.